Implementation of Administration in MIN 1 Medan - Jihan Fadhilah Taher; Candra Wijaya (Universitas Muhammadiyah Enrekang, 2023)
This study aims to (1) Describe how the implementation (implementation) of administration and (2) the constraints and solutions that exist in the implementation of administration in MIN 1 Medan. This research was conducted with a descriptive qualitative research approach. The informants of this study were madrasa heads, teachers, administrative staff and students. Data collection techniques used are interviews, observation, and documentation. Then the data were analyzed by interactive analysis which flowed with activities including data reduction, data display, and conclusion drawing/verification. Testing the validity of the data is done by triangulation of methods and sources. From the results of the study it can be concluded that: (1) The implementation of administration in MIN 1 Medan has been carried out properly and is organized as a function of the administration itself (2) Obstacles in the implementation of administration even if there are solutions can be found by first reflecting and evaluating.